Mental Health and Psychiatric Care - (:unkn) unknown (Routledge, 2024)
The WHO defines mental health as a “state of well-being in which every individual realises his or her own potential, can cope with the normal stresses of life, can work productively and fruitfully, and is able to make a contribution to her or his commu...
Keywords: Salud mental; Psiquiatría